Management of xerostomia using chlorine dioxide mouthwash in post-surgical and chemotherapy breast cancer patient with aromatase inhibitor treatment (anastrazole) - Perwiradinata, Ronden; Radithia, Desiana; Endah, Adiastuti; Soebadi, Bagus (Journal of Case Reports in Dental Medicine, 2020)
Objective: A 59-year-old woman with complaints of dry mouth, often feel thirsty, pain when swallowing, chapped lips, bleeding gums and bad breath. The patient had a history of breast cancer, underwent surgery and chemotherapy in 2010. The patient consumed 1 mg of Aromatase Inhibitors (AIs) tablets a day for 9 years.Methods: Patient underwent depression, anxiety and Stress Scale (DASS) questionnaire (Depression: normal; Anxiety: mild; and Stress: mild) and sialometry test (draining method) <0.1 ml/minute. Patient was diagnosed with xerostomia then instructed to use chlorine dioxide mouthwash 4 times a day. Management included anamnesis, clinical and laboratory examination: Complete Blood Count (CBC); Diabetic Profile; Lipid Profile; Renal Function Profile; and Tumour Marker test.Results: Patient’s sialometry test results in 1st, 2nd, 3rd and 4th visit are: 0.1ml/minute; 0.6ml/minute; 1.4ml/minute and 1.8ml/minute.Conclusion: Dentist has important role to evaluate and treat oral condition for optimal and comprehensive breast cancer treatment. Chlorine dioxide mouthwash is clinically proven to stimulate salivary gland in treating xerostomia.